Insight into molecular interactions and structural changes of ethyl lactate and (tri/tetra)-ethylene glycol binary mixture: A thermophysical and spectral depiction. (November 2022) - Kataria, Jyoti; Rani, Pooja; Devi, Pooja
Highlights: Variation in thermophysical properties on mixing ethyl lactate with glycol oligomers has been reported. Excess molar volumes have been analyzed through PFP theory and Graph theory. The structural variations of molecules in mixed state have been discussed. Spectroscopic studies have been performed to specify the interactions. Abstract: The current work deals with the analysis of the molecular interactions amongst the binary systems formed by significant solvents with environment friendly characteristics. The density ( ρ ) and refractive index ( n D ) of pure liquids and mixtures containing L-Ethyl Lactate (EL) + Tri-Ethylene Glycol (TrEG) or Tetra-Ethylene Glycol (TeEG) over the entire composition have been measured at four equidistant temperatures from T/(K) = 298.15 to 313.15 and pressure p /(MPa) = 0.1. Based on the experimental data, calculation of derived properties (excess molar volumes ( V m E ), partial molar volumes ( V ¯ m ), excess partial molar volumes ( V ¯ m E ), deviations in refractive index ( Δ ϕ n D ) and deviations in molar refraction ( Δ ϕ R M )) was done. The consequent properties were fitted to the Redlich-Kister polynomial equation to recognize the interaction coefficients and standard deviations. The obtained outcomes were examined theoretically through Prigogine-Flory-Patterson (PFP) theory and Graph theory to elucidate the non-ideal behaviour of investigated mixtures. The theoretical interpretations were found to be in harmony with experimental observations. Spectroscopic data from UltraViolet (UV) and Fourier Transform InfraRed (FT-IR) analysis ascertains the dominance of solute-solvent interactions in mixed state hereby supporting the experimental and theoretical analysis.